STUDI IMPLEMENTASI IZIN EDAR PRODUK PANGAN INDUSTRI RUMAH TANGGA (PIRT) DALAM MEWUJUDKAN KEAMANAN PANGAN YANG OPTIMAL DI KOTA SEMARANG - Bambang Hermanu (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
Health law definitely states that food and beverages can only be distributed in public upon issuance of a distribution permit. Hence, prior to being permitted the food and beverages are not allowed to be distributed in public. On the other hand, in line with the development of society, the rapid distribution of processed food (food and beverages), especially those produced as home industries, with or without packaging, has caused much concerns due to violation of the distribution permit and contamination of the products with its associated health risks in the short, medium, and long term. Normative and empirical legal research method has been employed for this research, using both primary and secondary data. The primary data were collected in the field; whereas the secondary data came from primary, secondary, and tertiary legal establishments, respectively. Results of this study showed that implementation of a distribution permit of food and beverages produced by home industries are in general the responsibility of the Office of Health in the City or Regency, with the issuance of Induction Certificates and Home Industry Products Certificates. These certificates are officially legal permits as a guarantee that the food and beverages produced by home industries are safe; and as a protection against food additives that could be detrimental to health. The implementation is basically a persuasive action under the assumption of human dignity rather than tough and normative legal procedures. Obstacles to the implementation included factors such as economic condition, inadequate knowledge of both consumers and producers, as well as the weak legal measures on food safety. A number of factors were found to affect the food safety in Indonesia, i.e. food system, culture, food chain, environment, nutrition and epidemiology. It was suggested that education forconsumers to raise awareness of food safety was of prime importance. Consumers should be made aware and fully understand the food safety system and its associated health risks due to insecure food safety.